2014
DOI: 10.1007/s11552-013-9578-6
|View full text |Cite
|
Sign up to set email alerts
|

Airbag-Induced Thumb Avulsion: Two Case Reports

Abstract: Although airbags are designed to save lives and protect victims from serious injuries, airbag deployment can cause unwanted lesions. In this case report, two cases are presented of young women who sustained an important fracture dislocation of the first carpometacarpal joint (CMC I joint) caused by airbag deployment during a car collision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The forces exerted by the inflating airbag can lead to various injuries in the upper extremities in spite of their protective purpose. The literature reports that injuries often occur when the arm is caught between the rapidly inflating airbag and the torso, when the limb is forcefully displaced during deployment, or when the hand is stuck in the spokes of the steering wheel [ 5 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The forces exerted by the inflating airbag can lead to various injuries in the upper extremities in spite of their protective purpose. The literature reports that injuries often occur when the arm is caught between the rapidly inflating airbag and the torso, when the limb is forcefully displaced during deployment, or when the hand is stuck in the spokes of the steering wheel [ 5 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Freedman's findings differ slightly, emphasizing the susceptibility of the first and fifth digits over more proximal injuries [ 12 ]. The spectrum of reported injuries encompasses abrasions, contusions, fractures, and burns [ 9 , 13–16 ], with the majority of injuries affecting soft tissues rather than bones [ 11 ]. In a comprehensive study by Jernigan et al.…”
Section: Discussionmentioning
confidence: 99%
“…These injuries can result directly from the impact of the airbag or indirectly if the airbag propels the extremity into another part of the vehicle interior, such as the dashboard, glove box, or steering wheel. The injury can be dramatic, as described by Stoel et al, 6 who reported 2 patients with open thumb carpometacarpal joint fracture-avulsion injuries. However, injuries can also be subtle and result in delayed diagnosis or treatment, and consequently disability and pain.…”
mentioning
confidence: 88%